Sectoral specialization and telework possibility: the case of Greek regions - Christofakis, Manolis; Ganapi, Maria (Bulletin of Geography. Socio-economic Series, 2025)
Research and policy efforts have focused on the expansion of teleworking over the last few years, especially during the Covid-19 pandemic. However, not all occupations and areas are suitable for teleworking. Using the Location Quotient and Pearson’s correlation coefficient index, this study examined the relationship between sectoral specialization and the possibility of telework at regional level in Greece, in order to identify the most suitable economic sectors and regions for telework. Spatial sectoral differentiation is related to the extent of telework diffusion, which appears to be more common in the tertiary sector. Teleworking appears to have exacerbated regional disparities in areas more specialized in trade and tourism activities. A contemporary digital strategy could contribute to a more balanced development of the country. These developments may reverse existing trends in the attractiveness of telecommuting in metropolitan areas and large urban centers.